Pengaruh Budaya Kerja dan Lingkungan Kerja Terhadap Kepuasan Kerja pada Pegawai Dinas Pendidikan dan Kebudayaan Kabupaten Pesisir Selatan - Dicky Pratama; Aldri Frinaldi (Jurusan Ilmu Administrasi Negara, 2022)
This research is trying to identify, and identify.whether there is a significant influence of work culture and work area on employee job satisfaction. This research was conducted at the Department of Learning and Culture of Pesisir Selatan Regency. This research uses a quantitative method with an associative approach. Determination of illustrations in this research is to use the Yamane formula in slovin language to obtain illustrations of 93 employees. Measurement of information was tried using a Likert scale. Information in this research was collected through questionnaires distributed to respondents. Information analysis was carried out using the classical assumption test.and multiple linear regression. The results of processing this information analysis show that there is a positive influence of work culture on employee job satisfaction. Adjusted R Square is 0.155%, a significance.value of 0.000 is smaller than 0.05. Work area has a significant effect on employee job satisfaction. Adjusted R Square is 0. , 286%. a significance value of 0, 000 is less than 0, 05. Simultaneously, work culture and work area have a significant effect on employee job satisfaction by 0, 313%, a significance value of 0, 000 is smaller than 0, 05.